2015
DOI: 10.1007/8904_2015_428
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Newborn Screening in a Healthy Infant of a Mother with Undiagnosed Medium-Chain Acyl-CoA Dehydrogenase Deficiency

Abstract: A neonate with low blood free carnitine level on newborn tandem mass spectrometry screening was evaluated for possible carnitine transporter defect (CTD). The plasma concentration of free carnitine was marginally reduced, and the concentrations of acylcarnitines (including C6, C8, and C10:1) were normal on confirmatory tests. Organic acids in urine were normal. In addition, none of the frequent Faroese SLC22A5 mutations (p.N32S, c.825-52G>A) which are common in the Danish population were identified. Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
0
6
1
Order By: Relevance
“…8,9 MCADD is a relatively mild fatty acid oxidation disorder (FAOD) and many affected individuals are asymptomatic and identified only on the diagnosis of metabolic defects in offspring and siblings. 10,11 The real prevalence of MCADD, however, could be higher than that suggested by the given data. Given that there is no evidence suggesting a certain ACADM genotype to be a safe one that offers protection from clinical symptoms, 12,13 even asymptomatic patients should be assessed.…”
contrasting
confidence: 67%
See 2 more Smart Citations
“…8,9 MCADD is a relatively mild fatty acid oxidation disorder (FAOD) and many affected individuals are asymptomatic and identified only on the diagnosis of metabolic defects in offspring and siblings. 10,11 The real prevalence of MCADD, however, could be higher than that suggested by the given data. Given that there is no evidence suggesting a certain ACADM genotype to be a safe one that offers protection from clinical symptoms, 12,13 even asymptomatic patients should be assessed.…”
contrasting
confidence: 67%
“…Interestingly, NBS could identify maternal MCADD: Aksglaede et al reported the case of an MCADD carrier infant with abnormal concentration of specific acyl-carnitines and low C0 (6.0 mmol/L), which contributed to the diagnosis of MCADD in the mother. 10 Importantly, false-positive and false-negative results can be observed on NBS. Very low-birthweight infants harboring a heterozygous pathogenic ACADM mutation are more likely to have elevated C8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in C6, C8, C10, with C8 most markedly, indicates medium-chain acyl-coenzyme A dehydrogenase (MCAD) deficiency 28 29 30) . Slightly elevated C8 of a neonate is also presented in MCAD deficiency carrier.…”
Section: Acylcarnitine As a Marker For Fatty Acid Oxidation Disorder mentioning
confidence: 99%
“…Curiously, levels of C5DC in the newborn are normal and what is usually observed is a secondary depletion of free carnitine levels [ 17 ]. Low levels of free carnitine on NBS have also been described in maternal carnitine transporter deficiency and maternal MCAD deficiency [ 18 ], which thus entails making a differential diagnosis among these disorders. In our experience, approximately half of the suspected cases of carnitine transporter defect in the newborn are of metabolic maternal origin.…”
Section: Discussionmentioning
confidence: 99%